The Hunger Games: linguistic modality as reflector of point of view in a dystopian novel - J. L. Christy, Jeyanthi Evelyn; Mohd Kasim, Zalina; Mohamad Ali, Afida; Ali Termizi, Arbaayah (Universiti Putra Malaysia Press, 2018)
Dystopian literature is a genre that imagines a futuristic universe in which oppressive societal control and the illusion of a perfect society are expressed. One famous novel of this genre is The Hunger Games written by Suzanne Collins (2008). Considering its strong social and pedagogical influences, an analytical study was considered necessary to investigate the linguistic modality of the novel. Modality refers to a speaker's opinion concerning the truth of a proposition. Hence, the primary goal of this study is to examine the linguistic manifestations of modality to identify point of view in the novel by determining the dominant modality shading. Simpson's (2005) framework was used as the analytical tool to conduct the analysis. The results indicate that epistemic modality is the most prevalent modality used in the novel and this has provided the novel with a negative shading. Furthermore, this accentuates notions of alienation and confusion within the narrative, by highlighting the narrator's struggles to make sense of what is happening. The results indicate that the narration reflects the character.